Study on the conversion mechanism of CO2 to O2 in pulse voltage dielectric barrier discharge at Martian pressure. (April 2023) - Fu, Qiang; Wang, Yufei; Chang, Zhengshi
Abstract: CO2 constitutes around 95 % of the atmosphere on Mars, and its in-situ utilization is of great value. O2 is a significant target product transformed from CO2 that can support both human respiration and fuel combustion, its conversion mechanism remains unclear. In this study, using a dielectric barrier discharge (DBD) with parallel plate electrodes, simulation and experimental results are combined to discuss the discharge characteristics and CO2 conversion process, under Mars conditions. The DBD was driven by a repetitive frequency microsecond pulse voltage. According to the discharge current, the discharge process can be split into four stages, namely the positive (negative) discharge stage and the positive (negative) discharge extinguishing stage. With a contribution up to 98 % and primarily taking place in the positive discharge extinguishing stage, the recombination decomposition reaction of electron and CO + 2 is the primary pathway of O2 synthesis. At the position near the edge of the cathode potential drop zone, electron impact ionization of CO2 ground state molecules dominates the formation of CO + 2 . Under the range of pulse parameters considered in this paper, increasing the pulse width can lengthen the time of recombination decomposition reaction of electron and CO + 2 in positive discharge extinguishing stage, which is favorable for the formation of O2 . Likewise, reducing the pulse's rising edge can increase the discharge intensity and CO + 2 density, which is also favorable to O2 production. Highlights: The discharge characteristics of DBD was analyzed, the plasma was further used to convert CO2 to O2 under Martian pressure. The main pathway to produce O2 is recombination decomposition reaction of e and CO + 2, with a contribution of more than 95 %. CO + 2 is mainly produced by electron impact ionization of ground state CO2 near the cathode drop region during discharge.